United States : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report, 1999)
This 1999 Article IV Consultation highlights that the U.S. real GDP grew by 3.9 percent in 1998, reflecting buoyant consumption and investment spending. In the first quarter of 1999, real GDP grew by 4.3 percent (annual rate) before slowing to 2.3 percent in the second quarter. Consumption has been boosted by a sharp fall in personal saving, with the ratio of personal saving to personal disposable income declining to 1\2 percent in 1998, and turning negative in the first quarter of 1999.